Is it Acceptable for a Psychologist to Break A Young Client Confidentiality? Comparing Latin American (Chilean) and Western European (French) Viewpoints (2014)
The views of Chilean and French adults concerning breaking confidentiality about illicit drug consumption were examined and compared. Twelve Chilean psychologists, 143 Chilean adults, and 100 French adults were presented with a series of 64 vignettes of a psychologist told by her young client that he is using illicit drugs. They were composed according to a six within-subject factor design: client’s age, dangerousness of the drug, duration of drug consumption, whether he agreed to be treated for addiction, stability of his family, and whether the psychologist consulted an expert before informing the family. Four qualitatively different personal positions were found, called Never acceptable (20% of the participants), Always acceptable (27%), Mainly depends on client’s age (20%), and Mainly depends on family problems (33%). A larger percentage of Chileans expressed the never acceptable view compared to French lay people, and a larger percentage of French expressed the mainly depends on client’s age view, compared to Chilean lay people. Chilean psychologists infrequently endorsed positions that are not fully compatible with the Chilean code of ethics.